Which Countries are Better Prepared to Compete Globally in the Disruptive Technology Age? : A Rapid, Forward-Looking Analysis of Countries' Share of the Global Private Sector - Mulas, Victor (World Bank, Washington, DC, 2018)
This note provides a rapid, forward-looking analysis of countries’ share of the global private sector. By using technology-enabled Unicorns as a leading indicator of the future’s global private sector, which is dominated by a technology platform business model of zero marginal costs and winner-takes-all dynamics, this analysis provides an indication of relative gains and losses of countries in the transition to a technology-driven new economy. The results are tested by comparing the gross domestic product (GDP) growth of countries and their relative position in this transition, which is then measured using a forward-looking approach. This analysis is a first approximation toward a predictive assessment and requires further research. However, the results provided in this note can help policy makers consider and assess new factors to deal with the uncertainties of disruptive technologies in their economies.